Differential geometry - Kreyszig, Erwin (Dover Publications, 1991)
Translation of: Differentialgeometrie; Originally published: Toronto : University of Toronto Press, 1959, in series: Mathematical expositions ; no. 11.; Includes bibliographical references (p. [343]-347) and index